2016
DOI: 10.1002/ijc.30506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statin on hepatocellular carcinoma in patients with type 2 diabetes: A nationwide nested case‐control study

Abstract: Relationship on new statin use and the risk of hepatocellular carcinoma (HCC) in patients with incident type 2 diabetes mellitus (T2DM), who might be at the risk of developing HCC, is uncertained. A nationwide population-based nested case-control study was conducted within the National Health Insurance Service National Sample Cohort 2002-2013 in Korea. Newly prescribed statin after newly diagnosed T2DM was defined as statin use. Controls were matched to case patients on age, sex, follow-up time, and the date o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 44 publications
3
52
0
Order By: Relevance
“…Previously, using a data source of 229 HCC case patients and 1,145 control cases, from patients with type 2 DM, statin initiation was reported to reduce the risk of incident HCC with an AOR of 0.36 (95% CI 0.22-0.60). 24 In the present study, we included the general population and examined the effect of statin use for HCC from the whole general population. In the DMmatched analysis, consistent with the previous results, the beneficial effect of statin use on HCC was greater in patients with DM, compared to subjects without DM, although DM alone was an increasing risk factor of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, using a data source of 229 HCC case patients and 1,145 control cases, from patients with type 2 DM, statin initiation was reported to reduce the risk of incident HCC with an AOR of 0.36 (95% CI 0.22-0.60). 24 In the present study, we included the general population and examined the effect of statin use for HCC from the whole general population. In the DMmatched analysis, consistent with the previous results, the beneficial effect of statin use on HCC was greater in patients with DM, compared to subjects without DM, although DM alone was an increasing risk factor of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that higher dosage and longer duration of statin use was associated with greater protective effects on the development of HCC. 104,107,[112][113][114] In contrast, Chiu et al showed that there was no significant doseresponse relationship in statin use and HCC development. 103 In vivo studies showed a dose-dependent effect of statin on angiogenesis, presenting a proangiogenic effect at low doses and an antiangiogenic effect at high doses of statin use.…”
Section: The Effect Of Statin Dosementioning
confidence: 97%
“…Several studies have demonstrated that the use of statins is inversely associated with the risk of incident HCC (►Table 2). [101][102][103][104][105][106][107][108][109][110][111][112][113][114] Using the Korean National Health Insurance Service Physical Health Examination Cohort from 2002 to 2013, 1,642 HCC cases were matched to 8,210 control individuals. 113 In this longitudinal nationwide nested casecontrol study, statin users had a 56% lower risk of HCC than nonusers.…”
Section: Evidence Of Hcc Prevention From Human Studies Epidemiologicamentioning
confidence: 99%
“…While a research study is designed to answer a specific research question, it is common for investigators to conduct subsequent analyses of subgroups in order to investigate associations in more detail. Some recent examples for the nested case-control design are the studies conducted by Devore et al, 61 Kim et al, 62 Boursi et al 63 and Liu et al 64 There is an abundant literature on subgroup analyses for randomised clinical trials. [65][66][67][68][69][70] The general advice, however, is to restrict subgroup analyses as much as possible, as the main issue is their overuse and over interpretation, in addition to the underuse of appropriate statistical tests for interaction.…”
Section: Motivationmentioning
confidence: 99%
“…As subgroup analyses are regularly performed in nested case-control studies [61][62][63][64] and as it remains unclear if these analyses can provide valid estimates, simulation studies were performed, which aimed to answer the following specific questions:…”
Section: Why Study IV Was Performedmentioning
confidence: 99%